DAMPAK PENGARUH GADGET TERHADAP INTERAKSI SOSIAL ANAK USIA DINI - Afdalia, Andi Puti; Gani, Irwanto (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2023)
This article discusses the impact of gadget usage on social interaction among young children using a phenomenological approach. The advanced era has elevated gadgets to a primary necessity, despite the presence of complex positive and negative effects. The role of parents as playmates has been replaced by gadgets, influencing social interactions among young children. This study employs a qualitative method involving centralized observation and interviews with parents as informants. The research findings reveal both positive and negative impacts. Positive impacts encompass the development of creativity, thinking skills, and children's self-confidence. However, negative effects involve social isolation, health disturbances, and addiction. Parents are advised to limit gadget usage time, implement balanced parenting styles, encourage social interactions, provide media literacy education, and set positive examples. In conclusion, the use of gadgets among young children should be managed wisely to foster holistic growth.